Community Pharmacists’ Roles in Providing Contraceptive Services: Views and Experiences of Adolescents in Urban Khon Kaen, Northeast Thailand - Andajani, Sari; Chanthasukh, Sansanee; Fairbairn-Dunlop, Peggy; Smith, John F (Oxford University Press, 2023)
OBJECTIVES: Adolescent pregnancy is a national public health priority in Thailand. While contraceptive methods are available to prevent adolescent pregnancy, Thai adolescent contraceptive usage is low. Community pharmacists are likely the first health professionals to contact adolescents engaged in unprotected sex and needing emergency contraception. However, there is limited research on Thai pharmacists' roles in promoting sexual and reproductive health. This study examines Thai adolescents' perspectives on community pharmacists' roles in promoting contraceptives and preventing unwanted pregnancies. METHOD: This qualitative study recruited 38 adolescents aged 15-19 from one vocational school and one secondary school in Khon Kaen, Thailand. Data were collected from focus group discussions and in-depth interviews and analysed using thematic analysis. KEY FINDINGS: Participants felt community pharmacists had potentially critical roles in promoting adolescent contraceptive use. Community pharmacists had relevant knowledge of effective contraceptive methods, the risks and benefits of each method, and the quality of different condoms available. Community pharmacists, at times, also provided emotional support to distressed adolescents who came to their store. However, participants reported pharmacists' age, gender, and non-empathetic and judgemental attitudes could be barriers to adolescents' ease of access to contraceptive services. CONCLUSION: This study highlights the potentially crucial role community pharmacists could play in providing contraceptive information for adolescents. It suggests the need for changes in government policies and education and training of community pharmacists to enhance their soft skills - empathetic and non-judgemental attitudes - and their roles in delivering youth-friendly sexual and reproductive health services.
Keywords: adolescents; community pharmacist; contraception; sexual health; Thailand; Thailand; adolescents; community pharmacist; contraception; sexual health; 3213 Paediatrics; 32 Biomedical and Clinical Sciences; Prevention; Clinical Research; Pediatric; Behavioral and Social Science; Health Services; Teenage Pregnancy; Contraception/Reproduction; Adolescent Sexual Activity; Reproductive health and childbirth; 3 Good Health and Well Being; 1115 Pharmacology and Pharmaceutical Sciences; Pharmacology & Pharmacy; 3214 Pharmacology and pharmaceutical sciences; Pregnancy; Female; Adolescent; Humans; Contraceptive Agents; Pharmacists; Thailand; Contraception; Focus Groups; Health Knowledge, Attitudes, Practice; Humans; Contraceptive Agents; Contraception; Focus Groups; Health Knowledge, Attitudes, Practice; Pregnancy; Adolescent; Pharmacists; Thailand; Female; Pregnancy; Female; Adolescent; Humans; Contraceptive Agents; Pharmacists; Thailand; Contraception; Focus Groups; Health Knowledge, Attitudes, Practice